Chapter 42 From Niche to Mainstream The Emergence of a Podcasting Culture and Market in the Italian Radio Context - PERROTTA, Marta (Taylor & Francis, 2022)
From being an amateur and niche practice, or a "simple" catch-up service for traditional radio stations, podcasting in Italy has rapidly grown in the last five years. This contribution analyses the evolution of the medium from niche to mainstream, in overlapping with the development lines of the radio market. I have been studying three shows in Italian ("Veleno", "La Piena" and "Morgana"), distributed by podcast platforms operating both in the national and in the international context, and one English-speaking show, developed by an Italian author. The study shows that the international models of audio storytelling resonate and are amplified in the national production. It also shows that, despite the absence of a professional sector dedicated to this medium, there is plenty of room to grow the offer of podcasts, in a country where radio listening, and the use of audio media are not losing ground compared to other forms of media consumption.